Work, health, and income among the elderly - Burtless, Gary T. (Washington, D.C .: The Brookings Institution, 1987)
The papers in this volume examine a range of issues affecting the current and future living conditions of the elderly. A topic of central interest is the health of the elderly and the implications of declining mortality rates for the future health and work capacity of older Americans.
Includes bibliographical references and index.
ne 17/05/2018
Loans
Keywords: Age and employment; Older people; Social security